Vehicular ad hoc networks and security issues: survey - Abdulkader, Zaid A.; Abdullah, Azizol; Abdullah, Mohd Taufik; Zukarnain, Zuriati Ahmad (Canadian Center of Science and Education, 2017)
Vehicular ad hoc network (VANET) technologies are evolving networked communications advances that incorporate mobile-based routing protocol sets for inter-vehicular exchanges of information in support of smart transportation networks. Privacy and security difficulties are primary concerns in VANET research as a result of the repeated vehicular movements, time-critical responses, and hybrid VANET architectures that differentiate these from other ad hoc networking types. Therefore, the design of secure mechanisms for authenticating and validating message transmissions between vehicles and eliminating adversarial elements from networks are of considerable importance in VANET research. This report offers a review of VANET features and security difficulties. The paper also summarizes certain chief threats to the authentication, confidentiality, and availability of secure services.